A Reference Framework of Software Development Practices Calibrated for Very Novice Programmers - Gutiérrez - Figueroa; Francisco (2023)
RESULTS OBTAINED: For each specific goal, describe or summarize the results obtained. Relate each one to work already published and/or manuscripts submitted. In the Annex section include additional information deemed pertinent and relevant to the evaluation process. The maximum length for this section is 5 pages. (Arial or Verdana, font size 10). In this project, we aimed to structure a reference framework of empirically tested software development practices calibrated for very novice programmers. The scope of the study population was limited to Chilean students aged between 10 to 12 years old with no prior background in computer programming and living in urban settlements. Although we initially intended to conduct in-person hands-on informal workshops to study the pertinence, acceptance, and effectiveness of incremental artifacts designed in the project, due to the socio-political upheaval in late 2019, as well as the continuous lockdowns and sanitary restrictions caused by the COVID-19 pandemic, we had to redesign said workshops to be conducted remotely. This introduced unexpected delays and tasks to be held throughout the project to obtain robust and sound empirical data. Nevertheless, we did our best efforts to comply with the original plan, in terms of research goals to address in this project. This document summarizes the main tasks that were fulfilled, as well as presenting the obtained results and manuscripts that are already published, under review, and planned to be submitted in the upcoming months. Research Goals (SG1) Propose a valid and reliable instrument to assess the development of computational thinking skills and the quality of software artifacts produced by very novice programmers, aged between 10 to 12 years old. In 2018, prior to this project, we developed a preliminary rubric for assessing the development of software development skills in projects developed in Scratch (a block-based language, considered as one of the main standards for introducing younger populations to coding), tailored to ...